A natureza jurídica dos regimes especiais tributários opcionais - Medeiros, Bruno Magno Herculano (2024)
The present work aims to investigate the legal nature of optional special tax regimes. These special regimes are extensive within Nacional Tax Legal System and have been subject to adjudication by the Superior Court of Justice and the Supreme Federal Court. The National Tax Legal System is composed of legal norms intended to collect taxes for public funds, representing a mandatory contribution from taxpayers as established by law. However, taxes are sometimes used for extrafiscal purposes, aiming to influence taxpayer behavior by affecting their freedom and autonomy. To achieve principles such as contributory capacity, practicality, or national development, the State has instituted optional special tax regimes that require specific counter-performances from taxpayers in order to receive tax benefits. Given the exercise of taxpayer autonomy and the reciprocal obligations between the State and taxpayers, these optional special tax regimes can be understood to possess the legal nature of a tax contract